EEF1A1 promotes colorectal cancer progression and predicts poor prognosis of patients. (24th May 2022) - Fan, A‐hui; Zhao, Xiaojuan; Liu, Hao; Li, Danxiu; Guo, Tongtong; Zhang, Jiehao; Duan, Lili; Cheng, Hao; Nie, Yongzhan; Fan, Daiming; Zhao, Xiaodi; Lu, Yuanyuan
Abstract: Colorectal cancer (CRC) is a major leading cause of cancer mortality worldwide in which dysregulated protein synthesis plays an etiologic role. The eukaryotic elongation factor 1 A1 (eEF1A1) exerts significant effects on protein synthesis by contributing to peptide chain extension. Whereas its role in CRC remains to be investigated. In this study, we found that the mRNA and protein levels of eEF1A1 were significantly upregulated in CRC cell lines and tissues. Elevated expression of eEF1A1 was correlated with shorter overall survival in 94 CRC patients. The inhibition of proliferation and cell cycle block were observed in CRC cells after eEF1A1 downregulation. Mechanistically, weighted gene correlation network analysis and further Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis suggested that mitogen‐activated protein kinases (MAPKs) signaling pathways were significantly enriched in high‐eEF1A1 expression group, and the levels of phosphorylated p38/JNK/ERK MAPK were dramatically decreased after eEF1A1 downregulation. Overexpression of eEF1A1 in CRC correlated with a poor prognosis. Collectively, this study determined the oncogenic role of eEF1A1 in CRC proliferation and tumorigenesis. eEF1A1 might be a promising therapeutic target and prognostic biomarker in CRC. Abstract : Through combining the analysis of cohorts in GEO database and in vivo and in vitro experiment, we report a novel oncogenic and prognostic role of eukaryotic elongation factor 1 A1 (eEF1A1) in colorectal cancer (CRC).